Electronic structure of hydrothermally synthesized single crystal U0.22Th0.78O2. Issue 10 (4th July 2016) - Turner, D. B.; Kelly, T. D.; Peterson, G. R.; Reding, J. D.; Hengehold, R. L.; Mann, J. M.; Kolis, J. W.; Zhang, X.; Dowben, P. A.; Petrosky, J. C.
Abstract : Single crystals of ThO2, UO2, and their solid solutions, U x Th1– x O2, have been obtained through various hydrothermal growth conditions. This technique offers the better of two other growth processes: (i) single crystal purity as by photochemical growth of nanocrystals; and (ii) large/bulk sizes as obtained by the arc melt method. The band gap of the U x Th1– x O2 single crystal solid solution, along with the luminescence transition, have been characterized. The occupied and unoccupied structures are determined using ultraviolet and inverse photoemission spectroscopy and the electronic band gap was measured to be 3–4 eV. The strain of incorporating U into the ThO2 is analyzed through Vegard's law. In this crystal there are defect and impurity sites, likely arising from the kinetic growth process, giving rise to a similar yet slightly different optical gap evident with cathodoluminescence spectroscopy. There is a major luminescence feature spanning the range from 3.18 to 4.96 eV (250–390 nm) with a maximum at 4.09 eV (303 nm), corresponding with the measured electronic band gap. In this paper, the electronic properties of a solid solution U0.22 Th0.78 O2 are measured and interpreted compared to the pure actinide oxides, ThO2 and UO2 .